Urbanization and risk preference in the People's Republic of China: A decomposition of the self-selection and assimilation effects - Xiaojun Shi; Zhu Yan (Asian Development Bank Institute (ADBI), 2017)
This paper argues that urbanization reshapes individual's risk preference by exerting self-selection and assimilation effects. Taking advantage of the unique hukou system in the People's Republic of China, we initiate a quasi-experiment method to elicit the two effects, employing the 2013-wave dataset of Chinese General Social Survey (CGSS). We find strong evidence supporting our two-effect theory and the magnitudes of both effects are sizable and near in scale. The assimilation effect reduces the migrant's risk aversion measurement by 0.606 while the self-selection effect reduces it by 0.715, on average. Overall, urbanization improves migrants' risk appetite, and mediated by this improvement, migrants are more likely to get engaged into the economic activities under uncertainty than their rural peers, as indicated by the evidence we have when applying the two-effect theory to investigate how households decide on risky financial asset investment.
Keywords: P25; R23; D1; J61; Q5; 330; risk aversion; migration; urbanization; assimilation; self-selection